2018
DOI: 10.20870/oeno-one.2018.52.1.1902
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl 2-hydroxy-3-methylbutanoate enantiomers: quantitation and sensory evaluation in wine

Abstract: Aim:To investigate chemical and sensory characteristics of ethyl 2-hydroxy-3-methylbutanoate in wines. Methods and results:Ethyl 2-hydroxy-3-methylbutanoate has been recently identified as a potential marker of lactic acid bacteria esterase activity. Enantiomers of this fruity ester were quantitated in 99 wines from various vintages and French regions using chiral gas chromatography (γ-cyclodextrin phase). Analyses revealed the predominant presence of the R enantiomer in red and white wines, with a maximum R/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The taste threshold of L-lactic acid was less than that of D-lactic acid, indicating that L-lactic acid is more acidic. This result suggests that the stereochemistry of the molecules has a strong influence on their perception [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The taste threshold of L-lactic acid was less than that of D-lactic acid, indicating that L-lactic acid is more acidic. This result suggests that the stereochemistry of the molecules has a strong influence on their perception [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The detection threshold of a compound is the concentration beyond which this molecule is perceived by one half of a panel. In oenology, detection thresholds have been measured, mainly on olfactory compounds, in different matrices such as water, wine, or spirits [29,30,32]. These studies have shown that the nature of the matrix can have a significant impact on the olfactory properties of a compound.…”
Section: Resultsmentioning
confidence: 99%
“…This enantiomer was quantified in various wines at concentrations higher than this value, demonstrating its contribution to wine bitterness [28]. Yet the sensory properties of a molecule, and in particular its detection threshold, can be strongly influenced by the nature of the matrix from an olfactory or gustatory point of view [29,30,31,32]. Consequently, the contribution of lignans to spirit taste cannot be presumed from the results obtained in wine.…”
Section: Introductionmentioning
confidence: 99%